Spatial Accessibility to Livestock Sanitary Infrastructure in the Kaniama-Kasese Site in Haut-Lomami Province, Democratic Republic of Congo: A GIS-Based Assessment of Veterinary Vulnerability - Alex, Mulongo Mbuya; Mululu, Patrick Ngoie; Francis, Lwapa Embele Isenge; Joachim, Umba di Mbalu; Freddy, Okitayela Onawoma; Paul, Monzambe Mapunzu; Nathan F, Nyongombe Utshudienyema (European Journal of Science, Innovation and Technology, 2026)
Livestock production in rural and peri-rural areas depends not only on herd size and grazing resources but also on access to essential sanitary infrastructure such as dipping facilities, veterinary clinics, watering points, and transport routes. This study analyzes the spatial accessibility of livestock sanitary infrastructure in the Kaniama-Kasese site in Haut-Lomami Province, Democratic Republic of Congo, using Geographic Information Systems (GIS), distance-based indicators, spatial autocorrelation, and multicriteria analysis. The analysis was based on georeferenced data for 23 kraals, 38 route segments, 24 points associated with watering infrastructure, one veterinary clinic, one existing dipping facility, and one visited kraal. Spatial analyses were conducted in a projected metric coordinate system (UTM Zone 35S). Indicators included kraal density, Euclidean distance to the nearest watering point, veterinary clinic, and dip, as well as proximity to the road network. Global and local spatial autocorrelation were used to examine the spatial structure of sanitary accessibility. A multicriteria sanitary vulnerability index was also developed by combining normalized distances to dips, watering points, and routes. The results show a low overall kraal density of 0.091 kraals/km² over a convex-hull area of 253.40 km². Mean distance from kraals to the nearest watering point was 1.70 km, whereas the mean distance to the veterinary clinic reached 8.99 km. Kraals were generally well connected to routes, with an average distance of only 0.04 km. In contrast, access to the existing dip was markedly unequal, with a mean kraal-to-dip distance of 8.70 km and strong positive spatial autocorrelation (Moran’s I = 0.584, z = 5.09, p < 0.001), indicating significant spatial clustering of sanitary disadvantage. A simulated second dip located in the most disadvantaged area reduced mean distance to dipping services to 6.22 km, corresponding to a reduction of 28.57%. Spatial clustering also decreased substantially, with Moran’s I falling from 0.584 to 0.352. This improvement was statistically significant according to both the paired t-test (p = 0.0017) and the Wilcoxon signed-rank test (p = 0.0039). These findings demonstrate the usefulness of GIS-based spatial analysis for identifying veterinary service gaps and supporting evidence-based planning of livestock sanitary infrastructure. The study provides a practical framework for improving spatial equity in animal health service provision in the Kaniama-Kasese site in Haut-Lomami Province.